Chronic fluoxetine treatment accelerates kindling epileptogenesis in mice independently of 5‐HT2A receptors. (1st June 2018) - Li, Crystal; Silva, Juliana; Ozturk, Ezgi; Dezsi, Gabriella; O'Brien, Terence J.; Renoir, Thibault; Jones, Nigel C.
Summary: Patients with epilepsy often have mood disorders, and these are commonly treated with antidepressant drugs. Although these drugs are often successful in mitigating depressive symptoms, how they affect the epileptogenic processes has been little studied. Recent evidence has demonstrated that treatment with selective serotonin reuptake inhibitor (SSRI) antidepressant drugs adversely promotes epileptogenesis, which may be of great concern considering the number of patients exposed to these drugs. This study investigated 5‐HT2A receptor signaling as a potential mechanism driving the pro‐epileptogenic effects of the prototypical SSRI fluoxetine. Male homozygous 5‐HT2A receptor knockout mice or wild‐type littermates (n = 9‐14/group) were treated with continuous fluoxetine (10 mg kg −1 d −1, sc) or vehicle and subjected to electrical kindling of the amygdala. Compared to vehicle, fluoxetine treatment accelerated kindling epileptogenesis ( P < .001), but there was no effect of genotype ( P = .75), or any treatment x genotype interaction observed ( P = .90). Of interest, fluoxetine treatment increased afterdischarge thresholds in both genotypes ( P = .007). We conclude that treatment with fluoxetine promotes epileptogenesis in mice, but this effect is not mediated by 5‐HT2A receptors. This suggests that antidepressants may accelerate the onset of acquired epilepsy in patients who have experienced epileptogenic cerebral insults.